Becalmed-off Gasparee, Trinidad - (:unkn) unknown (F.P. Bruce Austin, 2011)
The postcard shows a boat in the sea of the Gasparee Island, also known as Gaspar Grande, one of the Bocas Islands which lies 9 miles west of Port of Spain.
Colour: Sepia; Style:Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Sailboats--Trinidad and Tobago; Islands--Trinidad and Tobago; Gasparee; Gaspar Grande